Relación de la ingesta alimentaria y el estado nutricional en adultos con insuficiencia renal del hospital de Especialidades Abel Gilbert Pontón de la ciudad de Guayaquil. Noviembre 2023 - abril 2024. - Naranjo Rivera, Ruth Mercedes (2024)
Introduction: Chronic kidney disease is a major health problem that affects thousands of people globally and locally every year. This disease can affect the lives of those who suffer from it in many ways, including their dietary habits and intake. Objective: The objective of this study was to determine the relationship between dietary intake and nutritional status in adults with renal failure undergoing hemodialysis at the Abel Gilbert Pontón Hospital, Guayaquil, November 2023 - April 2024. Material and methods: A field, descriptive and cross-sectional study was carried out. Sixty-seven patients with chronic kidney disease who underwent treatment in the hemodialysis unit of the Abel Gilbert Pontón Hospital were analyzed. A survey was carried out to collect information on the main variable: frequency of consumption of different types of food. Results: The Pearson analysis shows a mostly positive relationship in most of the food groups, the main ones (positive relationship) being cereals, pastries, tubers, legumes and processed beverages. Those groups that do not maintain a strong relationship with respect to the patient's nutritional status (neutral relationship) are meats and fats, with a minimum influence. Conclusions: It was determined, by means of Pearson analysis, that the modified dietary intake in patients suffering from chronic renal failure is related to their nutritional status, with cereals, pastries, tubers, legumes and processed beverages being the groups analyzed with the highest relationship in this aspect.